Delineation of metals and radionuclides bioconcentration in eggs of seabream Sparus aurata and effect of environmental pCO2. (December 2018) - Lacoue-Labarthe, Thomas; Oberhänsli, François; Teyssié, Jean-Louis; Martin, Sophie
Abstract: Considered as the most vulnerable ontogenic stages to environmental stressors, the early-life stages of fish paid a peculiar attention with respect to their vulnerability to metal and radionuclides contamination. Concomitantly, the increasing anthropogenic CO2 release in the atmosphere will cause major change of the seawater chemistry that could affect the trace elements and radionuclides bioconcentration efficiencies by marine organisms. The aim of this work was to 1) delineate the uptake behaviours of Ag, Am, Cd, Co and Zn in seabream eggs during 65 h of development and retention by newly hatched and 7 h-old larvae maintained in clean seawater, respectively, and 2) investigate the effects of elevated p CO2 on the bioconcentration efficiencies of these elements in eggs. Besides differing in terms of maximal concentration factors values, the uptake kinetics showed element-specific patterns with Am being linearly bioconcentrated and Co and Zn showing a saturation state equilibrium. The 110m Ag and 109 Cd uptake kinetics shared a two-phases pattern being best described by a saturation equation during the first 24 h of development, and then an exponential loss of accumulated elements although the radiotracer concentrations in the surrounding water remained constant. At hatching time, the radioactivity of 110m Ag was the highest among radiotracers detected in the larvae. After 7 h in depuration conditions, 60% of this metal was still detected whereas 241 Am, 60 Co and 65 Zn were almost totally lost, suggesting an efficient incorporation of Ag in the embryo during the egg development. Finally, this study brought first qualitative data on the effect of p CO2 /pH on metal bioconcentration in eggs, raising the need to unravel chemical and biological processes to predict a potential shift of the toxicity of environmental contamination of fish early life stages with future ocean change. Highlights: The uptake of Ag, Am, Cd, Co and Zn has been delineated in seabream eggs. The 110m Ag is strongly accumulated and retained in embryo and larvae, respectively. We tested the effect of seawater acidification on radionuclides bioaccumulation. The 60 Co and 65 Zn concentration factors seem to be enhanced with increasing p CO2 . Our results raise the question of increased risk toward ionizing radiation for fish embryo.